PENGARUH KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN DENGAN KEPEMILIKAN MANAJERIAL SEBAGAI VARIABEL MODERASI - Romi Maulid Azhari; Maretha Ika Prajawati (Universitas Pendidikan Indonesia, 2022)
The purpose of this study was to determine the effect of financial performance on firm value, the effect of managerial ownership on firm value, and the effect of managerial ownership in moderating the relationship between financial performance and firm value. This study takes the object of a health sector company listed on the Indonesia Stock Exchange in 2019-2021. The method used in this study is a quantitative method with a total sample of 16 health sector companies listed on the Indonesia Stock Exchange. Based on statistical calculations, the results of the study show that financial performance has a significant effect on firm value, managerial ownership has no effect on firm value, and managerial ownership has no effect as a moderator of the relationship between financial performance and firm value.